Protection of Personal Rights in Distance Education Systems: Evaluation of Universities Regarding Coronavirus Disease (COVID-19) Process - Henkoğlu, Türkay; Şerefoğlu Henkoğlu, Halise (Information World, 2021)
Because of coronavirus (COVID-19) pandemic, universities have begun distance education through learning management systems (LMS). Protecting the personal rights of LMS users and ensuring their trust to these systems are seen as a prerequisite for the effectiveness and success of LMS. In this study, it is aimed to investigate the reflections of content used in LMS on the author, academic staff and students within the framework of personal rights protection, and to examine the responsibilities of distance education centers and information professionals taking part in these centers. For this purpose, personal rights for the use of LMS were examined and different LMS used by all universities in Turkey were compared with the legal conditions. In the study data were collected by examining the explanations, news and announcements, user manuals/guides, documents on the principles and procedures of distance education and the legal regulations regarding the personal rights of users published on web sites of 200 universities in Turkey. Based on collected data, the attitudes of universities towards the protection of personal rights, the compatibility between the approach for the protection of personal rights in the LMS is and legal regulations, and adequacy of security measures taken within the context of legal responsibilities for the protection of personal rights during the COVID-19 pandemic were investigated. The findings of the study show that, LMS solutions developed in the rapid transition to distance education are insufficient for protecting personal rights and there is an urgent need to set minimum security standards especially for data storage. In the final part of the study, attention was drawn to many different points that should be taken into consideration by the participants of LMS, who have different legal responsibilities, including students, academic staff, data controller, information professionals, distance education center officials and the Council of Higher Education.
Keywords: COVID-19; distance education; personal data; personal rights; Copyright